PENIGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI DINDING KATA (WORD WALL) - Mia Rachmawaty (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
This research motivated by the lack of teacher’s knowledge in the strategy of children beginning reading skills, because of that the ability on child's beginning reading skill are still low, there is no specific stimulation on the development of beginning reading skills that appropriate for children stages and ability, and also the process of reading lesson activities are still lead by the teacher as the center of activity, with one way mode trough the children. The purpose of this study is to improve the ability on children beginning reading by using word wall. This study uses an action research with two variables: the beginning reading ability (Y) and the word wall (X). The results showed an increase for overall percentage pre cycle only 30.8%, after the measures in the first cycle increased to 50.9%, and for the second cycle raised to 94.7%. From the second result, showed the highest percentage up to 100% was obtained by AI and QUI as the respondent and lowest percentage was 75 % obtained by JO as the respondent.